REVOLUSI MENTAL DALAM PENDIDIKAN UNTUK MEREVITALISASI NILAI-NILAI PANCASILA DAN MENUMBUHKEMBANGKAN WAWASAN KEBANGSAAN - Mulyasa, Enco (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The era of globalization is full of challenges and problems that develop more complex. It requires a mental revolution in various areas of life, including education. A mental revolution in education needs to be done to foster Pancasila values and national insights according to presidential instructions and regulations. Implementation of mental revolution in education, need to be supported by qualified human resources, especially teachers. Teachers have a very strategic role in the mental revolution and are very influential on the quality of education, so that, it needs the terms of personality and adequate ability with various capacities as professional.